Moral reasoning in e-learning generations: from 1.0 to 4.0 - Costa, Gonçalo Jorge Morais da (2014)
This paper explores two hot topics in e-learning literature: moral reasoning (bond to ethical and social issues) and its generations. Future educational environments impose a dramatic shift regarding “educational actors”, since include non-human agents. These novel “educational agents” promote unforeseen ethical and moral dilemmas which e-learning literature seems to disregard. Recent e-learning empirical data (second co-author PhD) serve as analytical starting point despite potential limitations. This paper is divided into three sections: guiding concepts (moral reasoning and elearning); ethical and social dilemmas- evaluating e-learning (authors’ argument and Stahl’s framework); and, analysis (disclosure, e-learning today and future e-learning).